Insulin resistance and brain-derived neurotrophic factor levels in chronic kidney disease. (March 2015) - Marchelek-Myśliwiec, Małgorzata; Cichocka, Ewa; Dziedziejko, Violetta; Dutkiewicz, Gra ż yna; Stępniewska, Joanna; Safranow, Krzysztof; Budkowska, Marta; Sałata, Daria; Syrenicz, Anhelli; Machaliński, Bogusław; Ciechanowski, Kazimierz
Introduction: Insulin resistance is a frequent abnormality in chronic kidney disease (CKD) appearing in early stages. Factors known to promote insulin resistance in CKD patients include disorders of ion and acid–base equilibrium and circulating uremia toxins. Recent research has focused on the central nervous system as the source of the brain-derived neurotrophic factor (BDNF). The aim of our work was to study plasma BDNF concentrations in stage 3 and 4 CKD patients in relationship with insulin resistance and distribution of adipose tissue. Method: Plasma BDNF concentrations were measured in a study group of 31 patients, including a subgroup of 20 non-diabetic subjects. Additionally dual-energy X-ray absorptiometry (DXA) was performed. Homeostatic model assessment of insulin resistance (HOMA-IR) and homeostatic model assessment of B-cell function (HOMA-beta) indices were calculated. Results: Two separate analyses were performed. In the first analysis performed in all 31 CKD patients, there were no correlations between BDNF and: body mass index (BMI), android, gynoid fat distribution, HOMA-IR and HOMA-beta. In the second analysis performed in 20 CKD patients without diabetes, BDNF was negatively related to gynoid fat (Rs = −0.47, P  = 0.034) and women revealed significantly lower levels of BDNF than men ( P  = 0.046). Normotensive patients disclosed significantly higher BDNF levels than hypertensive patients in the whole CKD group ( P  = 0.039) and in the non-diabetic subgroup ( P  = 0.028). No correlations between BDNF and eGFR were found. Conclusions: Female sex and arterial hypertension are associated with lower BDNF plasma concentration in CKD patients.